Strategi Promosi Melalui Pemanfaatan Media Sosial Instagram dalam Upaya Meningkatkan Volume Pengunjung: Studi pada D’livia Salon and Spa Surabaya - Kinanthi Nur Afifah Anastasya Rusmawan; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research uses descriptive research with a qualitative approach. This research aims to better explain promotional strategies through the use of Instagram social media in an effort to increase the volume of visitors to D'Livia Salon and Spa using the SWOT analysis method. The strategy carried out by D'Livia Salon n Spa Surabaya is considered good because the SWOT analysis of D'Livia Salon and Spa is located in quadrant I, namely by implementing an aggressive strategy. An aggressive strategy is producing a plan that requires strength to become an opportunity. This shows that D'Livia Salon and Spa has internal strengths that can be utilized to seize existing opportunities so that it can increase turnover and be able to compete in the business world in the beauty sector. When the application is successful, it results in an increase in the company's sales or income due to the increase in the number of visitors. According to the results of the analysis made using IFAS and EFAS while doing business, D'Livia Spa and Salon's strengths were given 2.20 points and its weaknesses were given 0.0.67 points. Dangers. received a total of 0 points. 64 and Opportunity received 2.37 points. According to the effects of the SWOT line, D'LiviaSalon and Spa is in the I quadrant with the value of (XY)(1.53:1.73) using aggressive planning. It requires the power of luck, which is the hardest way.